Scutellariae Radix and Citri Reticulatae Pericarpium Mixture Regulate PPARγ/RXR Signaling in Reflux Esophagitis. (4th January 2022) - Lee, Jin A.; Shin, Mi-Rae; Park, Hae-Jin; Roh, Seong-Soo
Abstract : Objective . Gastroesophageal reflux disease (GERD) is a gastrointestinal disorder in which stomach contents reflux into the esophagus, causing complications such as mucosal damage. GERD is a very common disease and is on the rise worldwide. The aim of this study was to assess the impact of a Scutellariae Radix and Citri Reticulatae Pericarpium mixture (SC) on esophageal mucosal injury in rats with chronic acid reflux esophagitis (CARE). Methods . After inducing reflux esophagitis through surgery, the group was separated and the drug was administered for 2 weeks: normal rats (Normal, n = 8), CARE-induced rats were treated with distilled water (Control, n = 8), CARE-induced rats were treated with vitamin E 30 mg/kg body weight (VitE, n = 8), CARE-induced rats were treated with SC 100 mg/kg body weight (SC100, n = 8), and CARE-induced rats were treated with SC 200 mg/kg body weight (SC200, n = 8). Results . SC treatment significantly reduced the degree of esophageal mucosal damage, significantly reduced levels of MDA and MPO, and inhibited the activation of the NF- κ B inflammatory pathway by activating the PPAR γ /RXR pathway. In addition, SC treatment significantly regulated the expression of arachidonic acid-related proteins (COX-1, COX-2, and PGE2 ) and modulated the MMP/TIMP proteins in reflux esophagitis. Conclusion . Consequently, SC improved the damage to the esophageal mucosa. Also, the anti-inflammatory effects of the SC suggested the inhibition of NF- κ B pathway through the activation of the PPAR γ /RXR pathway, thereby reducing the expression of inflammation-related cytokines.